2020
DOI: 10.3390/geosciences10020063
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Discrimination of Monazite Source Rock Based on Machine Learning Techniques and Multinomial Logistic Regression Analysis

Abstract: Detrital monazite geochronology has been used in provenance studies. However, there are complexities in the interpretation of age spectra due to their wide occurrence in both igneous and metamorphic rocks. We use the multinomial logistic regression (MLR) and cross-validation (CV) techniques to establish a geochemical discrimination of monazite source rocks. The elemental abundance-based geochemical discrimination was tested by selecting 16 elements from granitic and metamorphic rocks. The MLR technique reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Recently, various studies demonstrated the potentials of machine learning (ML) in the solution of petro‐volcanological problems (Bolton et al, 2020; Caricchi et al, 2020; Itano et al, 2020; Li et al, 2020; Petrelli et al, 2017; Petrelli & Perugini, 2016; Ren et al, 2019; Ueki et al, 2020). One common feature for ML models is that they do not need to solve complex problems using an a priori defined conceptual model (e.g., the definition of a thermodynamic reaction) but they can follow a data‐driven approach (Caricchi et al, 2020; Hazen, 2014; Hazen et al, 2019; Morrison et al, 2017) and unravel complexities in large data sets through a so‐called learning process (Shai & Shai, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies demonstrated the potentials of machine learning (ML) in the solution of petro‐volcanological problems (Bolton et al, 2020; Caricchi et al, 2020; Itano et al, 2020; Li et al, 2020; Petrelli et al, 2017; Petrelli & Perugini, 2016; Ren et al, 2019; Ueki et al, 2020). One common feature for ML models is that they do not need to solve complex problems using an a priori defined conceptual model (e.g., the definition of a thermodynamic reaction) but they can follow a data‐driven approach (Caricchi et al, 2020; Hazen, 2014; Hazen et al, 2019; Morrison et al, 2017) and unravel complexities in large data sets through a so‐called learning process (Shai & Shai, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The key mechanical properties of the native articular cartilages were extracted from the literature and summarized in table 3. The tensile strength, tensile modulus and elongation of the natural cartilages reported in table 3 are 35 MPa, 3-100 MPa and 2-140%, respectively 59 . However, under 15% less strain, the tensile modulus reaches only up to 5 to 10 MPa [44].…”
Section: Database Creationmentioning
confidence: 94%
“…The chemical composition of the monazite mineral determined using ED-XRF is given in Table [67]. It was proved that monazite chemical composition can be used as proxy of provenance and source rock type [68,69]. The variation in rare earth, Th, and U content is due to the presence of rocks act as provenance for heavy minerals, particularly monazite mineral.…”
Section: Geochemistry Of Monazitementioning
confidence: 99%